HISTORICAL STAGES OF THE DEVELOPMENT OF MILITARY SCIENCE: MILITARY SCIENCE OF THE NEW ERA (American Journal of Interdisciplinary Research and Development, 2023)
The rapid growth of the economy, especially in the second half of the 18th century, the growing contradictions between the emerging new bourgeois military system and the outdated feudal-absolutist one, the rapid development of natural and social sciences and their ever-increasing differentiation, the improvement of weapons and military equipment, the accumulation of experience of numerous wars – all this contributed to the activation of military-theoretical thought, required generalization and comprehension. In In Europe, this process developed in a complex and long way, contributing to the formation of military theory.